Transitive perfect colorings of 2-uniform tilings - Felix, Rene P.; Eclarin, Lawrence A. (2014)
In this work, a method to determine the nontrivial colorings of perfect and transitive 2-uniform tilings is presented. This method has been applied to determine all nontrivial transitive perfect colorings of 2-uniform tilings that use the least number of colors. In addition, the equivalence of the colorings obtained was also ascertained.
Keywords: Tiling (Mathematics); Symmetry; Polygons